2022
DOI: 10.1021/acsami.2c14029
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Artificial Synaptic Device Based on Amorphous InAlZnO Films for Learning Simulations

Abstract: Neuromorphic computing, which mimics brain function, can address the shortcomings of the "von Neumann" system and is one of the critical components of next-generation computing. The use of light to stimulate artificial synapses has the advantages of low power consumption, low latency, and high stability. We demonstrate amorphous InAlZnO-based light-stimulated artificial synaptic devices with a thin-film transistor structure. The devices exhibit fundamental synaptic properties, including excitatory postsynaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…It is concluded that the Al/Li 3 Sb 2 I 9 /ITO device shows competitive memory performance. Particularly, the Li 3 Sb 2 I 9 -based device exhibits the least numbers of voltage pulse to restore the “relearning” performance compared to that of other literature. ,, Therefore, the present Al/Li 3 Sb 2 I 9 /ITO device has a rapid response ability to simulate the memory function of human brains.…”
Section: Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is concluded that the Al/Li 3 Sb 2 I 9 /ITO device shows competitive memory performance. Particularly, the Li 3 Sb 2 I 9 -based device exhibits the least numbers of voltage pulse to restore the “relearning” performance compared to that of other literature. ,, Therefore, the present Al/Li 3 Sb 2 I 9 /ITO device has a rapid response ability to simulate the memory function of human brains.…”
Section: Results and Discussionmentioning
confidence: 84%
“…Synapses, as the most fundamental component of the biological brain, crucially contribute to learning and memory process due to their connections between presynaptic neurons and postsynaptic neurons. , Recently, the memristor has attracted great attention for its potential in simulating the behavior of the biological synapse owing to its adjustable conductance properties. Generally, the memristor possesses a sandwich structure consisting of two electrodes and a switching layer. The switching layer plays a dominant role in determining the state of conductance, reflecting the behavior state of the biological synapse. …”
Section: Introductionmentioning
confidence: 99%
“…The optical energy consumption per synaptic event of the synaptic is calculated to be 128 fJ, which is comparable favorably to most of optical-stimulated synaptic devices. [20,33] The incorporation of logic functions into synaptic device is essential for neuromorphic computing. [34,35] In complementary metal oxide semiconductor (CMOS) circuits, all logic gate can be formed with complementary pairs of p-MOS and n-MOS.…”
Section: Resultsmentioning
confidence: 99%
“…The optical energy consumption per synaptic event of the synaptic is calculated to be 128 fJ, which is comparable favorably to most of optical‐stimulated synaptic devices. [ 20,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] ReRAM is a device that uses changes in the resistance to store data, which are called resistive switching (RS) behavior. [5][6][7][8][9] Based on the metal conductive filament (CF) to realize the RS, the conductive-bridge ReRAM (CBRAM) is a very promising one in the next generation of non-volatile memory. [10,11] The diameter of the resistance wire can be only a few nanometers or even sub-nanometers.…”
Section: Introductionmentioning
confidence: 99%